Um estudo bibliográfico sobre o multiculturalismo no Ensino de Ciências e Biologia: o que dizem as pesquisas na área - Ferreira, Janielly Mendes (Universidade Federal do Tocantins, 2023)
The decolonial approach has emerged as a critical and transformative perspective, challenging established paradigms in education and academic research. The general objective of this research is to recognize and verify how the theme of decoloniality of traditional peoples is being treated in the main journals in the area of Science and Biology Teaching. Accordingly, the specific objectives are: to identify scientific productions on ethnic-racial, quilombola and indigenous education in journals in the area of Science and Biology Teaching and to analyze scientific productions related to ethnic-racial, quilombola and indigenous education in research published in the main journals in the area of Science and Biology Teaching from the last 5 years (2018-2022). The development of this work was based on the following questions, in the area of Science and Biology Teaching: how are scientific productions/research on ethnic-racial, quilombola and indigenous education being developed?; What is being addressed in these scientific productions on this topic? The methodology used was qualitative-quantitative, in which the searches for works were carried out using descriptors and to facilitate the analysis and discussion of the data, these searches were classified into categories. Data analysis took place in dialogue with the theoretical framework. It is concluded that there is a small number of works on this topic in the main journals in the area of Science and Biology Teaching, but that in the last year there has been a significant increase in this number. It also allows us to understand that these works are more concentrated in the Southeast and Northeast Regions, mostly focused on Basic Education, focused mainly on the teaching-learning process, criticizing Eurocentris.